Delayed structural maturation of inner hair cell ribbon synapses in a mouse model of fragile X syndrome - Chojnacka, M.; Skupien-Jaroszek, A.; Dziembowska, M. (Frontiers in Molecular Neuroscience, 2025)
Clinical features of the fragile X syndrome (FXS) phenotype include intellectual disability, repetitive behaviors, social communication deficits, and, commonly, auditory hypersensitivity to acoustic stimuli. Electrophysiological studies have shown that FXS patients and Fmr1KO mice exhibit improper processing of auditory information in the cortical areas of the brain and the spiral ganglion of the cochlea. Synapses formed by spiral ganglion neurons on sensory hair cells (HC) are the first connection on the path that conveys the auditory information from the sensory cells to the brain. We confirmed the presence of fragile X mental retardation protein (FMRP) in the inner hair cells of the cochlea. Next, we analyzed the morphology of IHC ribbon synapses in early stages of postnatal development (P5, P14) and detected their delayed structural maturation in Fmr1 KO mice. Interestingly, the ultrastructure of inner hair cell ribbon synapses, studied by electron microscopy in adult mice (P48), has shown no specific dysmorphologies. Delayed structural maturation of presynaptic ribbons of auditory hair cells in Fmr1 KO mice may contribute to abnormal development of circuits induced by auditory experience.